Adolescent pregnancy in the time of COVID-19: what are the implications for sexual and reproductive health and rights globally? - Okeke, Sylvester R.; Idriss-Wheeler, Dina; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2022)
Abstract The COVID-19 pandemic has aggravated pre-existing challenges associated with adolescents’ sexual and reproductive health and rights (SRHR). Evolving evidence suggest that it could adversely impact the progress made towards improving sexual and reproductive health outcomes among young people. The pandemic has stalled achievements in reducing adolescent pregnancy and child marriage by reinforcing contextual and structural determinants of these reproductive health outcomes, especially among girls. The pandemic has increased disruptions to schooling, decreased access to sexual and reproductive health services and compounded pre-existing socio-economic vulnerabilities. The consequences of neglecting adolescent sexual and reproductive health services over the past 2 years, to focus on COVID-19, continue to emerge. This commentary argues for targeted and responsive approaches to adolescent SRHR that tackle preventable consequences resulting from inequities faced by adolescents globally, particularly girls.